Exploring the validity of the Stokes–Einstein relation in supercooled water using nanomolecular probes. Issue 45 (8th September 2021) - Berkowicz, Sharon; Perakis, Fivos
Abstract : We investigate the diffusive dynamics of nanomolecular probes in supercooled water and find that, contrary to pure water, the Stokes–Einstein relation is preserved for probes independent of size, from 100 nm to ≈1 nm polyhydroxylated fullerenes. Abstract : The breakdown of Stokes–Einstein relation in liquid water is one of the many anomalies that take place upon cooling and indicates the decoupling of diffusion and viscosity. It is hypothesized that these anomalies manifest due to the appearance of nanometer-scale spatial fluctuations, which become increasingly pronounced in the supercooled regime. Here, we explore the validity of the Stokes–Einstein relation in supercooled water using nanomolecular probes. We capture the diffusive dynamics of the probes using dynamic light scattering and target dynamics at different length scales by varying the probe size, from ≈100 nm silica spheres to molecular-sized polyhydroxylated fullerenes (≈1 nm). We find that all the studied probes, independent of size, display similar diffusive dynamics with an Arrhenius activation energy of ≈23 kJ mol −1 . Analysis of the diffusion coefficient further indicates that the probes, independent of their size, experience similar dynamic environment, which coincides with the macroscopic viscosity, while single water molecules effectively experience a comparatively lower viscosity. Finally, we conclude that our results indicate that the Stokes–Einstein relation is preserved for diffusion of probes in supercooled water T ≥ 260 K with size as small as ≈1 nm.